A high‐throughput ultrasonic spraying inoculation method promotes colony cultivation of rare microbial species. (12th January 2021) - Huang, Xizhi; Li, Pengjie; Zhou, Mengfan; Li, Yiwei; Ou, Xiaowen; Chen, Peng; Guggenberger, Georg; Liu, Bi‐Feng
Summary: Current method for obtaining microbial colonies still relies on traditional dilution and spreading plate (DSP) procedures, which is labor‐intensive, skill‐dependent, low‐throughput and inevitably causing dilution‐to‐extinction of rare microorganisms. Herein, we proposed a novel ultrasonic spraying inoculation (USI) method that disperses microbial suspensions into millions of aerosols containing single cells, which lately be deposited freely on a gel plate to achieve high‐throughput culturing of colonies. Compared with DSP, USI significantly increased both distributing uniformity and throughput of the colonies on agar plates, improving the minimal colony‐forming abundance of rare Escherichia coli mixed in a lake sample from 1% to 0.01%. Applying this novel USI to a lake sample, 16 cellulose‐degrading colonies were screened out among 4766 colonies on an enlarged 150‐mm‐diameter LB plate. Meanwhile, they could only be occasionally observed when using commonly used DSP procedures. 16S rRNA sequencing further showed that USI increased colony‐forming species from 11 (by DSP) to 23, including seven completely undetectable microorganisms in DSP‐reared communities. In addition to avoidance of dilution‐to‐extinction, operation‐friendly USI efficiently inoculated microbial samples on the agar plate in a high‐throughput and single‐cell form, which eliminated masking or out‐competition from other species in associated groups, thereby improving rare species cultivability.